HIV/AIDS beliefs among MSM in the Philippines - Decoste, Anthony (Stellenbosch : Stellenbosch University, 2015)
ENGLISH ABSTRACT: This research study examines the beliefs related to HIV/AIDS risks and the perceived effectiveness of preventative measures among men who have sex with men (MSM) in the Philippines. Using a questionnaire developed using the Health Belief Model (HBM), this study endeavors to understand beliefs and thus improve counseling guidelines for MSM who continue to engage in risky sexual behaviors following VCT and a negative HIV test. The impact of HIV/AIDS on the Philippines is beginning to increase, affecting men and their partners. The rapid growth of HIV/AIDS among Filipino MSM indicates that more attention must be paid to the barriers and benefits of condom use within this high-risk population. A background of the presence and prevalence of HIV/AIDS is presented. This study aims to answer the question of why MSM choose to have unprotected sex despite the risk of HIV/AIDS. Multiple barriers to condom use are identified, including the availability of condoms, partner resistance, and reduced pleasure. The impacts of culture and society, the media, role models, social networking, drug use, and riskseeking behavior on safer sex are assessed. Currently, supplying condoms and providing voluntary testing and counseling is the primary mode of preventing the spread of HIV/AIDS, but this study sheds light on the critical issues of condom availability, perceived benefits and barriers to condom use, and the disconnect between belief and behavior regarding HIV/AIDS and unprotected sex among MSM in the Philippines.